Retrospective analysis of factors associated with quetiapine dosage in the acute and subsequent six-month maintenance treatment of bipolar disorders - Zhang L (Dove Medical Press, 2013)
Ling Zhang, Gang Wang, Jiong Luo, Qing-E Zhang, Qian Zhao, Qi-Ying Deng, Xin Ma Mood Disorders Center, Beijing Anding Hospital, Capital Medical University, Beijing, People’s Republic of China Background: Although quetiapine has often been used as monotherapy or adjunctive therapy in bipolar disorder, there is very limited clinical evidence regarding prescribing practices for quetiapine as maintenance treatment for bipolar disorder. Methods: We reviewed the inpatient and outpatient records of 175 Chinese patients who received treatment with quetiapine for bipolar disorder both during and following hospitalization. We compared patients treated with high-dose (>300 mg/day) and low-dose (≤300 mg/day) quetiapine during the acute treatment phase and in the subsequent 6 months of maintenance treatment, with assessments at months 1, 3, and 6. Multifactor logistic regression analysis was performed to identify factors associated with quetiapine dosage. Results: The proportion of patients receiving combination therapy of quetiapine and a mood stabilizer as acute and maintenance treatment was 99.4% and 84.6%, respectively. The mean dose of quetiapine when used for acute treatment in the 175 patients was 395.7 mg/day. The following factors were found to be independently associated with use of high-dose quetiapine: male gender (odds ratio [OR] 2.712, 95% confidence interval [CI] 1.372–5.362, P < 0.01), a manic or mixed episode (OR 2.786, 95% CI 1.362–5.699, P < 0.01), and psychotic features (OR 2.658, 95% CI 1.318–5.361, P < 0.01). In the subsequent 6 months, the mean dose of quetiapine prescribed steadily decreased to 375.0 mg/day, 330.6 mg/day, and 293.7 mg/day at months 1, 3, and 6. The main factors associated with high-dose quetiapine in maintenance treatment were male gender (month 1, OR 2.761; month 3, OR 2.583; month 6, OR 2.686; P < 0.01) and a manic or mixed episode (month 1, OR 2.626; month 3, OR 2.334; P < 0.01). Conclusion: Higher doses of quetiapine (>300 mg/day) are more likely to be prescribed to patients who are male, those who are experiencing a manic or mixed episode, and those who have psychotic features during acute treatment of bipolar disorder. For patients who remain clinically stable during the subsequent months, the quetiapine dose should be adjusted according to patient gender and the most recent type of episode experienced. Keywords: quetiapine, bipolar disorder, acute treatment, maintenance treatment, dosage